Macroglossia and outcome of severity based treatment regime - Kumar, Umesh; Huded, Vijaykumar; Bera, Sudipta; Jain, Pradeep; Sarkar, Arnab; Sharma, Yasharth (International Surgery Journal, 2021)
Background: This study aims to categorize macroglossia patients into mild, moderate, and severe groups and formulate a treatment plan depending upon the severity of tongue involvement. Methods: Eight patients presented with macroglossia between 2018 and 2020 are reviewed retrospectively. The patients were categorized into three subgroups depending upon the clinical presentation and subjected to either sclerotherapy or surgical debulking. The clinical outcome as a reduction of size and symptomatic improvement were analyzed and categorized after a minimum of 6 months follow-up. Results: Eight patients (5 males and 3 females) aged 10-40 years with a mean age of 28.25 (SD 10.29) years were included in the study. Of eight patients, four cases were of vascular malformation, three of neurofibroma, and one was due to amyloidosis. Four patients were treated with surgery, three with sclerotherapy while one patient was managed with combined modalities. On average, 58% and 28% volume reduction were achieved with surgery and sclerotherapy respectively. Excellent, very good, and good results were obtained in 1, 3, and 4 cases respectively. Pain (2/8), edema (2/8), and distal congestion (1/8) were noted as a complication. Conclusions: Macroglossia results from various causes and the common cause being VM. Surgery and sclerotherapy are the mainstay treatment for such a condition. They remain effective when used alone or in combination and also in a staged manner depending upon the severity of macroglossia.